MENINGKATKAN ASPEK KESELAMATAN PADA SISTEM INJEKSI BAHAN KIMIA DENGAN MENGGUNAKAN METODE TEE LESS DI INDUSTRI HULU MIGAS - Swandito, Adji (IDENTIFIKASI, 2020)
Leakage at access fitting of injection point chemical has created a potential environmental pollution and safety risk for workers due to chemical and hydrocarbon spills. The purpose of this study is to analyze the causes of leakage and improve the reliability of the access fitting chemical injection system using the PDCA method. Analysis of the causes of leakage was carried out using Fishbone, FMEA, and Pareto method. The results of this study showed that leakage in the access fitting injection system was caused by the galvanic corrosion mechanism. Modification and innovation result in the access fitting injection system using tee less method have succeeded in eliminating the galvanic effect that causes corrosion. The improvement process of the access fitting injection system using tee less method has met five quality targets including zero spill, zero leaking accident, cost savings, fast installation, and increased confidence in the reliability of the chemical injection system.